196k views
5 votes
Steps to sloving -2(x+3)=-10​

User Mishmash
by
4.9k points

2 Answers

5 votes

Answer:

x = 2

Explanation:


-2(x+3)=-10 divide both sides by (-2)


(-2(x+3))/(-2)=(-10)/(-2)


x+3=5 subtract 3 from both sides


x+3-3=5-3


x=2

User Shotmeinthehead
by
5.8k points
3 votes

Answer:

x = 2

Explanation:

It is given an expression with variable x

-2(x + 3) = -10​

To find the steps to solving expression

Le expression be,

-2(x + 3) = -10​

-2x + (-2 * 3) = -10

-2x - 6 = -10

-2x = -10 + 6

-2x = -4

2x = 4

x = 4/2 = 2

Therefore x = 2

User Vadersfather
by
6.4k points